1998
DOI: 10.1002/(sici)1521-4141(199805)28:05<1544::aid-immu1544>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The nature of antigen in the eye has a profound effect on the cytokine milieu and resultant immune response

Abstract: The eye is endowed with a number of mechanisms that protect it from immune-mediated injury. One such mechanism, termed anterior chamber-associated immune deviation (ACAID), evokes the antigen-specific, systemic down-regulation of Th1 responses to antigen inoculated into the anterior chamber of the eye. ACAID has been correlated with the selective production of IL-10 by the antigen-presenting cells (APC) and the development of a cross-regulatory Th2-like response. A small subset of antigens do not induce ACAID,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The nature of the molecular interactions underpinning the formation of NC1 dimers has been extensively studied in the homologous (␣1␣2␣1) 2 hexamers, but the detailed mechanism remains unknown. A subset of M-␣1␣2␣1 hexamers composed of ␣1 and ␣2 NC1 monomers exists in the bovine lens capsule basement membrane, and dimer-rich D-␣1␣2␣1 hexamers are predominant in the placenta basement membrane (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the molecular interactions underpinning the formation of NC1 dimers has been extensively studied in the homologous (␣1␣2␣1) 2 hexamers, but the detailed mechanism remains unknown. A subset of M-␣1␣2␣1 hexamers composed of ␣1 and ␣2 NC1 monomers exists in the bovine lens capsule basement membrane, and dimer-rich D-␣1␣2␣1 hexamers are predominant in the placenta basement membrane (24).…”
Section: Discussionmentioning
confidence: 99%
“…Privilege originally implied a location anatomically protected from attack by the immune system, such as the eye, brain, or testes (1). It is now recognized that the pathophysiology of protectiveness involves multiple mechanisms, including cytokines that inhibit innate or adaptive immunity (2), systemic regulatory T cells (3), and local cytotoxic mechanisms producing apoptosis of effector T cells induced by local FasL-Fas interactions (4). What has not been widely appreciated is that the molecular sequestration of self-antigen in complex structures can be a critical mechanism of immunologic privilege.…”
mentioning
confidence: 99%
“…However, the suppression of IgG and IgM Ab responses in that study was due to IFN-␥ produced by Qa-1-restricted CD8 ϩ regulatory T cells (10). By contrast, ACAID involves the down-regulation of IFN-␥ and a concomitant induction of IL-10 production (31)(32)(33). In other systems, Qa-1-restricted CD8 ϩ regulatory T cells have been shown to down-regulate Th1 immune responses and mitigate Th1-mediated autoimmune diseases, such as experimental allergic encephalomyelitis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…31 However, particulate or cell-associated antigens may also induce IL-12 and Th1 responses after anterior chamber injection. 32 The posterior part of the eye also appears to have immune deviant features. Streilein et al 30,33,34 reported an immune-deviant response against soluble and cell-bound antigens in the subretinal space.…”
Section: Immune Response To Intraocular Delivery Of Viral Vectors J Bmentioning
confidence: 99%